GLOBAL RESEARCH TRENDS OF SCIENTIFIC PUBLICATIONS ON HALAL FOOD SUPPLY CHAIN: A BIBLIOMETRIC ANALYSIS - Cindy Nurul Aulia Putri; M. Ruslianor Maika (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The halal food supply chain attracts significant interest from researchers and practitioners globally, especially in Muslim-majority countries. Method: This study maps and analyzes existing halal food supply chain literature using a bibliometric approach with RStudio and the Bibliometrix package through Biblioshiny. Results: Results reveal that 2024 saw the highest number of publications, with 234 documents. Universiti Putra Malaysia is the top institution, and Khan S. is the most prolific author. Malaysia, China, and Indonesia lead in scientific output on this topic. Novelty: This research deepens understanding of trends in halal food supply chain studies and lays a foundation for further research. It also encourages exploration of integrating technological innovation and Sharia values into global halal logistics and supply chain systems.